Two new species of the genus Metaxonchium Coomans & Nair, 1975 (Nematoda, Dorylaimida, Belondiridae) from Vietnam - Nguyen, Thi Anh Duong; Peña-Santiago, Reyes (Zootaxa, 2018)
Two new species of the genus Metaxonchium are described from natural habitats of Vietnam. Metaxonchium bonkowskii sp. n. is characterized by its 1.69–2.23 mm long body, lip region offset by weak constriction and 9.5–10.5 µm broad, odontostyle 11–13 µm long, neck 673–868 µm long with the pharyngeal expansion occupying 66–77% of its length, anterior genital branch reduced to a uterine sac 75–135 µm long or 4–7% of body length, posterior uterus tetrapartite and including a Z–like differentiation, V = 51–55, and female tail short and rounded (37–51 µm, c = 66–97, c’ = 0.5–0.7). Metaxonchium silvaticum sp. n is characterized by its 1.28–1.43 mm long body, lip region offset by weak depression and 7.0 µm broad, odontostyle 8–9 µm long, neck 502–630 µm long with the pharyngeal expansion occupying 65–76% of its length, anterior genital branch reduced to a uterine sac 65–80 µm long or 4–6% of body length, posterior uterus tripartite, non-echinophor, V = 52–57, tail short and rounded (18–23 µm, c = 56–74, c’ = 0.6–0.8) with abundant blister–like or saccate bodies, spicules 41 µm long, and seven spaced ventromedian supplements.